Conservation and evolutionary divergence in the activity of receptor-regulated smads - Sorrentino, Gina M (BioMed Central, 2012)
BACKGROUND: Activity of the Transforming growth factor-β (TGFβ) pathway is essential to the establishment of body axes and tissue differentiation in bilaterians. Orthologs for core pathway members have been found in all metazoans, but uncertain homology of the body axes and tissues patterned by these signals raises questions about the activities of these molecules across the metazoan tree. We focus on the principal canonical transduction proteins (R-Smads) of the TGFβ pathway, which instruct both axial patterning and tissue differentiation in the developing embryo. We compare the activity of R-Smads from a cnidarian (Nematostella vectensis), an arthropod (Drosophila melanogaster), and a vertebrate (Xenopus laevis) in Xenopus embryonic assays. RESULTS: Overexpressing NvSmad1/5 ventralized Xenopus embryos when expressed in dorsal blastomeres, similar to the effects of Xenopus Smad1. However, NvSmad1/5 was less potent than XSmad1 in its ability to activate downstream target genes in Xenopus animal cap assays. NvSmad2/3 strongly induced general mesendodermal marker genes, but weakly induced ones involved in specifying the Spemann organizer. NvSmad2/3 was unable to induce a secondary trunk axis in Xenopus embryos, whereas the orthologs from Xenopus (XSmad2 and XSmad3) and Drosophila (dSmad2) were capable of doing so. Replacement of the NvSmad2/3 MH2 domain with the Xenopus XSmad2 MH2 slightly increased its inductive capability, but did not confer an ability to generate a secondary body axis. CONCLUSIONS: Vertebrate and cnidarian Smad1/5 have similar axial patterning and induction activities, although NvSmad1/5 is less efficient than the vertebrate gene. We conclude that the activities of Smad1/5 orthologs have been largely conserved across Metazoa. NvSmad2/3 efficiently activates general mesendoderm markers, but is unable to induce vertebrate organizer-specific genes or to produce a secondary body axis in Xenopus. Orthologs dSmad2 and XSmad3 generate a secondary body axis, but activate only low expression of organizer-specific genes that are strongly induced by XSmad2. We suggest that in the vertebrate lineage, Smad2 has evolved a specialized role in the induction of the embryonic organizer. Given the high level of sequence identity between Smad orthologs, this work underscores the functional importance of the emergence and fixation of a few divergent amino acids among orthologs during evolution.